A comparison of ultrasound with magnetic resonance imaging in the assessment of fetal biometry and weight in the second trimester of pregnancy: An observer agreement and variability study. (November 2018) - Matthew, Jacqueline; Malamateniou, Christina; Knight, Caroline L; Baruteau, Kelly P; Fletcher, Tara; Davidson, Alice; McCabe, Laura; Pasupathy, Dharmintra; Rutherford, Mary
Objective: To compare the intra and interobserver variability of ultrasound and magnetic resonance imaging in the assessment of common fetal biometry and estimated fetal weight in the second trimester. Methods: Retrospective measurements on preselected image planes were performed independently by two pairs of observers for contemporaneous ultrasound and magnetic resonance imaging studies of the same fetus. Four common fetal measurements (biparietal diameter, head circumference, abdominal circumference and femur length) and an estimated fetal weight were analysed for 44 'low risk' cases. Comparisons included, intra-class correlation coefficients, systematic error in the mean differences and the random error. Results: The ultrasound inter- and intraobserver agreements for ultrasound were good, except intraobserver abdominal circumference (intra-class correlation coefficient = 0.880, poor), significant increases in error was seen with larger abdominal circumference sizes. Magnetic resonance imaging produced good/excellent intraobserver agreement with higher intra-class correlation coefficients than ultrasound. Good interobserver agreement was found for both modalities except for the biparietal diameter (magnetic resonance imaging intra-class correlation coefficient = 0.942, moderate). Systematic errors between modalities were seen for the biparietal diameter, femur length and estimated fetal weight (mean percentage error = +2.5%, −5.4% and −8.7%, respectively, p  < 0.05). Random error was above 5% for ultrasound intraobserver abdominal circumference, femur length and estimated fetal weight and magnetic resonance imaging interobserver biparietal diameter, abdominal circumference, femur length and estimated fetal weight (magnetic resonance imaging estimated fetal weight error >10%). Conclusion: Ultrasound remains the modality of choice when estimating fetal weight, however with increasing application of fetal magnetic resonance imaging a method of assessing fetal weight is desirable. Both methods are subject to random error and operator dependence. Assessment of calliper placement variations may be an objective method detecting larger than expected errors in fetal measurements.